Open Praxis vol. 12 issue 4 - Inés Gil-Jaurena (ed.), various authors (Open Praxis, 2020)
The last Open Praxis issue in 2020 includes nine research papers and one book review. It also includes the list of reviewers who have collaborated in reviewing the papers submitted to Open Praxis volume 12.